Isolation and characterization of Methicillin-Resistant Staphylococcus Aureus (MRSA) and Methicillin-Susceptible Staphylococcus Aureus (MSSA) clinical isolates in Terengganu - Ainal Mardziah Che Hamzah
Staphylococcus aureus is one of the most common nosocomial pathogen encountered in the healthcare settings and is especially known for its ability to develop and acquire antimicrobial resistances. The emergence of multi drug resistant (MDR) strains such as methicillin-resistant S. aureus (MRS A) is of particular concern due to the challenge it poses to treatment management. Furthermore, MRS A has now become endemic in most Asian hospitals. The present study is aimed to evaluate the current trends in antimicrobial resistance among S. aureus clinical isolates in Terengganu, Malaysia. A total of 260 not repeated S. aureus isolates were collected from Hospital Sultanah Nur Zahirah (HSNZ), the main tertiary hospital in Terengganu, from July 2016 to June 2017. Antibiotic resistance towards 18 antimicrobial classes encompassing 26 antibiotics targeting S. aureus were screened based on international antimicrobial susceptibility testing guidelines. The susceptibility tests were carried out using the Kirby-Bauer disc diffusion method and minimum inhibition concentration (MIC) values for tigecycline and vancomycin were determined using e-test strips. The prevalence of the macrolide-lincosamide-streptogramin B (MLSB) resistance phenotypes, i.e., inducible (iMLSB), constitutive (cMLSB) or macrolide-streptogramin (MS) phenotypes among S. aureus isolates was determined using the D-z ne test. Strains were validated as MRSA by cefoxitin resistance and presen of the mecA gene. The clinical data of each isolates were also obtained. Of the 260 S. aureus isolates, 112 were MRSA and 148 were methicillin-susceptible S. aureus (MSSA). Majority of the isolates were obtained from pus (62.3%, 162/260) followed by blood (28.9%, 75/260) and patients more than 50 years in age were particularly the most affected (35.8%, 93/260). Generally, MRSA isolates displayed higher level of resistance to multiple antibiotics compared to MSSA. No vancomycin-resistant isolate was detected. Five MRSA isolates were tigecycline-resistant, which is rarely reported and is a cause of concern. The iMLSB phenotype was observed predominantly among MRSA isolates, with 45.5% (511112) MRSA isolates as compared to 2.0% (3/148) MSS i lut s. H pital-acquired strains were the dominant circulating strains (67.8%) compared t the community-acquired strains (32.2%). Even so, some of the community strains were also able to cause serious diseases such as infective endocarditis, necrotizing enterocolitis and necrotizing fasciitis. Patients who were infected with MRSA isolates had significantly longer median hospital stay (10 days) compared to MSSA (6 days; p = 0.008). Fatal cases of both MRSA and MSSA were reported in older patients with bloodstream infections. The prevalence of MDR was much higher among MRSA isolates (82.1 %, 921112) compared to MSSA (10.8%, 161148). Although vancomycin-resistant isolates were not detected in any of the S. aureus isolates, infection control and preventative measures should not be taken lightly as the high prevalence of MDR as well as the occurrence of serious diseases indicated that S. aureus can still present enormous challenge to health. The high incidence of MDR and the iMLSB phenotype and the emergence of tigecyclineresistant S. aureus isolates in Terengganu warrant continuous vigilance.